Implementasi Teori Concret-Pictorial-Abstract (CPA) pada Pembelajaran Luas Permukaan Bangun Ruang untuk Pembelajaran Bermakna - Furqoni, Azka Nadiya El; Noviartati, Kurnia; Zahri, Mohammad (Jurnal PEKA (Pendidikan Matematika), 2026)
Inappropriate teaching methods are one of the reasons students face difficulties in learning geometry. This study was designed to describe the implementation of the CPA theory and student learning outcomes  within the framework of meaningful learning on the topic of surface area of three-dimensional shapes among eighth-grade students at SMP Al Maahira IIBS Malang. The research approach applied was a mixed  methods approach, with a convergent design selected. Data collection was conducted through observations and test results. The research instruments used in this study were observation sheets and test sheets. The results showed that the implementation of the CPA theory in teaching the surface area of three-dimensional shapes for meaningful learning was carried out very well, with an average observation score of 96.15%. Meanwhile, the test results showed that 10 out of 21 students (47.62%) achieved a score meeting the “Excellent” criterion, 9 students (42.86%) met the “Good” criterion within a certain score range, while 2 students (9.52%) obtained a score meeting the “Fair” criterion. Thus, the percentage of students’ learning outcomes in the “Good” and “Very Good” categories was 90.48%. Based on the results of this study, the implementation of the CPA theory—structured through three interrelated stages—demonstrates that students were able to master geometric concepts in a structured manner, beginning with the observation of concrete objects, the creation of visual representations, and culminating in the application of mathematical symbols. Meaningful learning occurs when students discover the differences between real-world objects and the nets of cubes and rectangular prisms; this indicates a process of conceptual understanding through direct experience. This is supported by test results showing that 90.48% of students achieved the “Good” and “Very Good” categories.